Internalization of Local Cultural Values Mototabia in Maintaining Press Ethics in North Bolaang Mongondow Regency - Gumohung, Wiranto; Subhan, Andi; Akasse, Cahyadi Saputra; Ratnasari, Dwi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The role of the press is vital in maintaining the truth in information dissemination. Strong press ethics and journalist integrity are needed to maintain accurate, objective, and ethical information. The press certainly has an increasingly crucial role in shaping public views on various issues. Indonesia is rich in different and highly valued cultural backgrounds. The identity of the press is reflected in the cultural practices applied in its professional activities. This study examines the internalization of local Mototabia cultural values in maintaining press ethics in the North Mongondow Regency. This study applies a qualitative-descriptive method with primary data collection through observation and in-depth interviews. Informants selected are based on press criteria bound by press ethics and are part of Mongondow cultural practices, in this case, Mototabia. This study indicates that the internalization of local Mototabia cultural values that contain goodness can strengthen the press in North Bolaang Mongondow Regency in maintaining press ethics and building better relationships with the local community. The internalization of Mototabia cultural values in a member of the press can be beneficial in the context of press ethics. Local cultural values integration not only increases public trust in the press but also creates awareness of the ethics that must be maintained in conveying information for the common good.